VITAMIN D STATUS AND ITS EFFECT ON FUNCTIONAL OUTCOME IN PATIENTS WITH HIP FRACTURE: AN OBSERVATIONAL STUDY - KARAN HINGANKAR; AVINASH KEDARI; RAJ PRAMOD GANDHI; RAHIL JIWANI (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The study aimed to study the Vitamin D status of adult patients presenting with hip fractures and analyze potential impact of Vitamin D status on outcome of these patients. Methods: This was an observational study of Vitamin D status of patients presenting with hip fractures. It was conducted in the department of orthopedics of a tertiary care medical college. One hundred and twenty adult patients presenting with hip fractures were included in this study on the foundation of a predefined inclusion and exclusion criteria. Demographic details of all the patients such as age, gender, and socioeconomic status were noted. Vitamin D status of patients was determined and correlated with functional outcome at the time of final follow-up visit at 6 months. Results: Among the 120 studied with hip fractures, 64 cases (53.33%) involved females, while 56 cases (46.67%) involved males having a M: F ratio of 1:1.14. The mean age of male and female patients was found to be 45.85±10.12 and 46.74±9.86 years. Overall, 65 (54.17%) patients were Vitamin D sufficient and remaining 55 (45.83%) were either inefficient (26.67%) or deficient (19.17%). Seventy-three (60.83%) patients had excellent to good outcome whereas 31 (25.83%) patients had fair outcome. Out of remaining 16 patients, 11 (9.17%) patients had poor outcome and 5 (4.17%) patients had very poor outcome. The patients with sufficient Vitamin D status were found to have a better outcome as compared to those patients with inefficient or deficient Vitamin D status and the difference was found to be statistically significant (p=0.01). Conclusion: It is significant to treat Vitamin D deficiency in patients presenting with hip fractures as Vitamin D deficiency is associated with suboptimal functional outcome in cases with hip fractures.